Experimental and DFT studies on Hexacoordinated acyl(alkyl)and Pentacooordinated Hydroxyalkyl(phosphinite)erhodium(III). Catalytic Hydrolysis of Ammonia Borane. Issue 9 (16th February 2021) - Azpeitia, Susan; Mendicute‐Fierro, Claudio; Huertos, Miguel A.; Rodríguez‐Diéguez, Antonio; Seco, José M.; Mota, Antonio J.; Garralda, María A.
Abstract: [Rh(nbd)Cl]2 (nbd=norbornadiene) reacts with quinoline‐8‐carbaldehyde (C9 H6 NCHO) and pyrazole (Hpz) affording, depending on Rh/Hpz ratio, acyl‐alkyl [Rh(μ‐Cl)(C9 H6 NCO)(Hpz)(σ‐C7 H9 )]2 (1 ) or [RhCl(C9 H6 NCO)(Hpz)2 (σ‐norbornenyl)] (2 ), stereoselectively as confirmed by DFT calculations. Hydrogen bond between NH‐pyrazole and O‐acyl occurs. 1 and 2 react with diphenylphosphine oxide (SPO) giving 16e [RhCl(C9 H6 NC(nbyl))(Ph2 PO)(Hpz)] (3 ) through SPO κ 1 ‐P‐coordination, C−C bond coupling between acyl and norbornenyl and outer‐sphere O(P)‐to‐O(C) hydrogen transfer. 3 shows distorted trigonal bipyramidal structure with weak intramolecular (C)−OH⋅⋅⋅O(=P) and NH⋅⋅⋅Cl hydrogen bonds. DFT calculations indicate this 16e structure being favoured by σ‐ and π‐type orbital multi‐overlapping between pyrazole and both the OH⋅⋅⋅O and chlorine and by intermolecular forces in the crystal. Solutions of 3 contain an equilibrium between trigonal bipyramid and a square‐planar pyramid with OH interacting with phosphoryl and NH, confirmed by DFT 13 C NMR calculations. 1 is very efficient homogeneous catalyst for H3 N−BH3 hydrolysis to release hydrogen under air. Abstract : Acyl‐pyrazole complex efficient homogeneous catalyst for hydrolytic H2 release from ammonia‐borane. PPh2 (O)promotes tandem C−C coupling/outer sphere hydrogen transfer and stable pyrazole 16e species. DFT studies allow understanding experimental X‐ray structures and observed species in solution.